Detection of EGFR-TK Domain–activating Mutations in NSCLC With Generic PCR-based Methods. Issue 3 (March 2015) - Shahi, Rajendra B.; De Brakeleer, Sylvia; De Grève, Jacques; Geers, Caroline; In't Veld, Peter; Teugels, Erik
<x xml:space="preserve">Abstract</x> Somatic mutations in the epidermal growth factor receptor-tyrosine kinase (EGFR-TK) domain of non–small cell lung cancer (NSCLC) influence the responsiveness of these tumors to EGFR-TK inhibitors, indicating their usefulness as a predictive molecular marker. However, for mutation analysis, the amount of clinical material available from NSCLC patients is often very limited, suboptimally preserved, and composed of both normal and tumor cells. As a consequence, the total amount of recovered DNA is frequently very limited, with mutant alleles being often strongly underrepresented, and thus requiring highly sensitive methods for the detection of mutations. In the present study, EGFR mutation screening was performed on 210 NSCLC clinical samples by heminested polymerase chain reaction (PCR), followed by denaturing gradient gel electrophoresis (DGGE). Candidate mutations were further characterized by sequencing. Seventeen different types of pathogenic EGFR-TK domain mutations were detected in 55 of the 210 samples (26%). We reanalyzed 149 of the 155 samples in which no mutation was found by real-time PCR for the presence of recurrent exon 21 and exon 19 mutations using peptide nucleic acid probes in the PCR mix to increase sensitivity by mutant allele enrichment. Four additional samples with exon 19 mutations were detected. Thus, it is found that the relatively simple and inexpensive PCR-DGGE assay is already very sensitive for the detection of mutations in clinical samples, including samples with low tumor cellularity (10% or higher tumor cell content), although the sensitivity and speed of the assay can be further increased for a restricted panel of mutations by introducing peptide nucleic acid probes in the DGGE or real-time PCR–based assay.